A graduação em Fisioterapia no contexto da formação de profissionais para o sistema de saúde no Brasil : um olhar sobre o curso da Universidade Federal de São Carlos - Almeida, Aline Barreto de (Universidade Federal de São Carlos, 2011)
The aim of this study is contribute to knowledge production in Physiotherapy Graduation field according to the recent health professional preparation policies and indentifies the suitable strategic planning in order to insert the professionals in this local context. Therewith, studies about Physiotherapy professional preparation at the Federal University of São Carlos (UFSCar) was performed, relating its history face to the trajectory of public health policies and the current training of health workers for Sistema Único de Saúde (SUS). This investigation keeps a single and qualitative feature, and it is also in process. Therefore, directed interviews were conducted individually with professors of the Physiotherapy course and focused groups with students. The data collection was made by the course coordinator, the head of department, nine teachers and thirty- two students. Furthermore, it was used as a technique of research, documentaries and observation with daily field reports. The analysis used the dialectic-hermeneutic approach, based on six categories: political and pedagogical project, pedagogical approach, practice settings, teacher capacity, labor world and the construction of switches. As a result, it was found that the recent history of this studied course portrays a lack of effective participation in discussions and actions in face of the Health Care Reform and the construction of SUS, which produced a gap between physical therapy and public health. While the discussions of policies for training health professionals were directed to an expansion of activity with the SUS approximation, the Physiotherapy preferred scientific investigation as propulsion for its recognition. Current policies to encourage new practices and curricular changes, which we can branch the National Curriculum Guide; have produced interesting effects on the course, providing an effective teachers preparation and the inclusion of students in the health town network. We conclude that the journey since the collection to data analysis of training methods in physiotherapy course at UFSCar added to the literature about the significance of changes on the way to provide greater proximity to health needs and the SUS. The thematic of Physiotherapy preparation is still an incipient subject. It is important consider the efforts of those who learn with it is new and make changes as a result of hard work and long battles, from the opening and meetings of presidential scenarios, from the new networking assembled and thoughtful discussions among various stakeholders within and outside the university.
The Physiotherapy graduation in context of professional preparation to the health Brazilian system: the final term research at the Federal University of São Carlos
Keywords: Saúde pública; Fisioterapia; Formação profissional; Políticas públicas; Physiotherapy; Professional preparation; Public Policies; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL